The meaning of being human for the nursery students under the sight of complexity - Juliana Aparecida Ribeiro; Francisca Georgina Macedo de Sousa; Keyla Cristiane do Nascimento; Gabriela Marcelino; Alacoque Lorenzini Erdmann (Rev Rene)
The purpose of this exploratory, qualitative study was to comprehend the meaning of "being human" as explained by the Nursing students of a Federal University in the south of Brazil. The data was obtained through interviews, based upon the guiding question, "What does Being Human mean to you?" The data was collected, analyzed, grouped, and its content was accordingly identified into the following five categories: social beings, beings of totality, faith beings, beings to themselves and to others, and complex beings. In an effort to better comprehend humanity, it is beneficial to classify humans as complex beings, and understand them according to certain innate characteristics as well as certain characteristics that are developed through survival efforts. This article concludes that humans perceive one another according to their own needs and individualities. It is a necessary attribute for future care-givers to respect individual beings in their complexity.